2008
DOI: 10.1016/j.jpba.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The direct comparison of health and ulcerated stomach tissue: A multiple probe microdialysis sampling approach

Abstract: The ability to directly compare gastric ulcerated and healthy tissue would aid in the understanding of the physiological differences between these tissue types. Presently, these comparisons can only be drawn by the use of separate animal groups, which results in increased study variability. The focus of this research was to develop a four-probe microdialysis sampling approach to directly compare ulcerated and healthy tissue in the same animal. After controlled chemical ulcer induction, probes were implanted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This fourprobe microdialysis sampling was used to directly compare drug absorption between gastric ulcerated and healthy tissue in the same animal, where the dialysate was analysed using high performance liquid chromatography ultraviolet (HPLC-UV). The study showed a higher drug concentration in ulcer tissue, which was a function of ulcer size and thickness and probe location within the tissues when compared to healthy tissue (112). The reconstructed oesophagus of patients undergoing resection of carcinoma was monitored with microdialysis to investigate the risk of postoperative complications caused by ischemia.…”
Section: Microdialysis Monitoringmentioning
confidence: 99%
“…This fourprobe microdialysis sampling was used to directly compare drug absorption between gastric ulcerated and healthy tissue in the same animal, where the dialysate was analysed using high performance liquid chromatography ultraviolet (HPLC-UV). The study showed a higher drug concentration in ulcer tissue, which was a function of ulcer size and thickness and probe location within the tissues when compared to healthy tissue (112). The reconstructed oesophagus of patients undergoing resection of carcinoma was monitored with microdialysis to investigate the risk of postoperative complications caused by ischemia.…”
Section: Microdialysis Monitoringmentioning
confidence: 99%
“…Later, the same group demonstrated the use of a linear probe for transdermal delivery studies [25,181] . This same probe design was then widely utilized for studies of various tissues, including liver [182] , tumor [183] , stomach [10,11] , and muscle [184] .…”
Section: Representative Applications Of MD To Pharmaceutical Analysismentioning
confidence: 99%
“…By 2007, microdialysis had evolved enough as a tool for pharmacokinetic and drug metabolism studies that the U.S. Food and Drug Administration sponsored a workshop on the role of microdialysis in the drug evaluation process [41] . Recently, Woo and Lunte used multiple probes to monitor the absorption of caffeine by a healthy versus ulcerated stomach in a rat model [10,11] . Figure 19 shows the average caffeine concentration in the blood and in ulcerated and healthy stomach tissue following an oral dose of caffeine.…”
Section: Representative Applications Of MD To Pharmaceutical Analysismentioning
confidence: 99%
See 2 more Smart Citations